Latar as the Central Point of Houses Group Unit: Identifiability for Spatial Structure in Kasongan, Yogyakarta, Indonesia - Subroto, T. Yoyok Wahyu (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2012)
The massive spatial expansion of the city into the rural area in recent decades has caused such problems as related to the spatial exploitation in villages surrounding. This raises a question of whether the open space change into land coverage building may have a spatial structure implication on settlement growth and evolution process in the villages surrounding. This paper reports a case study of Kasongan village in Bantul regency, Yogyakarta, Indonesia in between 1973-2010 in which the problem refers to the discussion of spatial structure is rarely addressed especially in village’s settlement growth and evolution analysis. The bound axis which consists of 4 (four) quadrants and one intersection refers to the reference axes in a Cartesian Coordinate System (CCS) is used to analyze the setting of the houses group unit around 4 areas/ quadrants. Through such spatial process analysis by means spatial structure approach, the continuity of latar (yard), in the central of houses group unit is detected. There is finding from this research that the latar which exists in ‘the central point’ of houses group unit in Kasongan during 4 decades significantly becomes the prominent factor of the basic spatial structure. It composes the houses group unit in Kasongan.